Effective use of geothermal energy for hydrogen production: A comprehensive application - Karayel, G. Kubilay; Javani, Nader; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
The present study aims to investigate the geothermal energy potential for green hydrogen production in Turkey. Geothermal energy potential varies based on each city's location and underground resources (particularly on their flowrates, temperatures and composotion). Alkaline electrolysers (ALELs) are considered for water splitting and hence hydrogen production. The total hydrogen production potential for Turkey using geothermal resources is estimated to be 559.76 kilotons. In this regard, Aydin, Manisa, and Denizli appear to be the cities with the largest hydrogen production potentials. Hydrogen generation potentials for all Turkish cities are provided and discussed for a feasible hydrogen economy. It furthermore gives a countrywide spectrum of how an effective role geothermal energy can play in making the country leader in this field. The study results may serve as a good base for planning and strategizing purposes as required for the country and help in developing new energy policies for exploiting renewable energy resources.
Keywords: Green hydrogen; Geothermal energy; Renewable energy; Flash power generation; Electrolyser; EXERGY; ELECTROLYSIS; PLANTS; Thermodynamics; Energy & Fuels